2021
DOI: 10.1177/0956797620975781
|View full text |Cite
|
Sign up to set email alerts
|

Aging Increases Prosocial Motivation for Effort

Abstract: Social cohesion relies on prosociality in increasingly aging populations. Helping other people requires effort, yet how willing people are to exert effort to benefit themselves and others, and whether such behaviors shift across the life span, is poorly understood. Using computational modeling, we tested the willingness of 95 younger adults (18–36 years old) and 92 older adults (55–84 years old) to put physical effort into self- and other-benefiting acts. Participants chose whether to work and exert force (30%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(88 citation statements)
references
References 50 publications
4
73
0
Order By: Relevance
“…To derive the best estimates of each individual’s willingness to invest effort, we fit participants’ choices to three functions that are commonly used to model effort discounting—linear, parabolic, and hyperbolic. These model comparisons revealed that participants’ choices were best fit by a parabolic pattern of effort discounting (AIC: parabolic = 4544, linear = 4787, hyperbolic = 5329; BIC: parabolic = 5042, linear = 5285, hyperbolic = 5826), which is consistent with previous work 36 , 52 , 53 , 64 , 69 , 70 . We then extracted the k -values for each participant from the winning model, and correlated them with ratings on the apathy and fatigue inventories.…”
Section: Resultssupporting
confidence: 88%
“…To derive the best estimates of each individual’s willingness to invest effort, we fit participants’ choices to three functions that are commonly used to model effort discounting—linear, parabolic, and hyperbolic. These model comparisons revealed that participants’ choices were best fit by a parabolic pattern of effort discounting (AIC: parabolic = 4544, linear = 4787, hyperbolic = 5329; BIC: parabolic = 5042, linear = 5285, hyperbolic = 5826), which is consistent with previous work 36 , 52 , 53 , 64 , 69 , 70 . We then extracted the k -values for each participant from the winning model, and correlated them with ratings on the apathy and fatigue inventories.…”
Section: Resultssupporting
confidence: 88%
“…Do older people exert more prosocial effort than younger people (Lockwood et al, 2021)? Does high talker variability in training examples make it easier for non-native speakers to learn Mandarin tones (Dong et al, 2019)?…”
Section: Introductionmentioning
confidence: 99%
“…After a literature study regarding several variables considered rational to be used as determining factors in prosocial action, model specifications were adopted in several studies. Some of the variables adopted are gender (Kamas & Preston, 2021;Rietveld et al, 2013), Age (Lockwood et al, 2021), Education (Umar et al, 2021;Smith, 2016;Rietveld et al, 2013, Employment (Smith, 2016, length of stay (Allen, 2018), and expenses (Clotfelter & Steuerle, 1981;James & Sharpe, 2007). This study includes the variable of family size that explains the number of dependents.…”
Section: Discussionmentioning
confidence: 99%
“…Someone with older age will have a higher prosocial value (Jin et al, 2021). Compared to younger people, older people are more willing to help others and exert the same power on themselves and others (Lockwood et al, 2021). This is based on the premise that older people become more prosocially motivated.…”
Section: Individual Factors In Prosocial Behaviormentioning
confidence: 99%